PERANAN KEPOLISIAN RESOR LABUHAN BATU TERHADAP TINDAK PIDANA PENCURIAN DENGAN KEKERASAN - ROBERTUS A PANDIANGAN (Universitas Sumatera Utara, 2013)
Police force, an important element in creating security and order, provides protection, service, and shelter to people. Violent theft criminal acts in Police jurisdiction of Labuhan Batu increases, either quantitatively or sadistically so that they even cause death. Police jurisdiction of Labuhan Batu comprises three districts: Labuhan Batu Induk/Raya District, Labuhan Batu Utara District, and Labuhan Batu Selatan District.The violent theft criminal acts in Article 365 of the Penal Code are regulated specifically on robbery. One factor which causes them in the Police jurisdiction of Labuhan Batu is that the number of the police personnel is not balanced with the wide area. Therefore, it prioritizes the handling of them as the prominent case. It is recommended that the sanctions imposed on the perpetrators collectively be based on Article 365 and Article 56 of the Penal Code, these factors should be efficiently, and the priority scale on violent theft criminal acts should be increased. Keywords: Role of Police Force, Police District of Labuhan Batu, Violent Theft Criminal Act